2022
DOI: 10.3389/fonc.2022.803824
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography/Magnetic Resonance Imaging Radiomics in Predicting Lung Adenocarcinoma and Squamous Cell Carcinoma

Abstract: ObjectiveTo investigate the diagnostic value of positron emission tomography (PET)/magnetic resonance imaging (MRI) radiomics in predicting the histological classification of lung adenocarcinoma and lung squamous cell carcinoma.MethodsPET/MRI radiomics and clinical data were retrospectively collected from 61 patients with lung cancer. According to the pathological results of surgery or fiberscope, patients were divided into two groups, lung adenocarcinoma and squamous cell carcinoma group, which were set as po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…The results were consistent with those of Orlhac et al (21), who found that scaly cell carcinoma had lower homogeneity and higher entropy by comparing the texture characteristics of ADC and SCC. Moreover, it was consistent with our previous findings (15) in that PET/MRI was used to create a prediction model for the pathological subtypes of ADC and lung SCC. It was also found that the GLSZM-GLN feature value accounted for the maximum weight ratio, indicating that ADC was more homogeneous than SCC.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The results were consistent with those of Orlhac et al (21), who found that scaly cell carcinoma had lower homogeneity and higher entropy by comparing the texture characteristics of ADC and SCC. Moreover, it was consistent with our previous findings (15) in that PET/MRI was used to create a prediction model for the pathological subtypes of ADC and lung SCC. It was also found that the GLSZM-GLN feature value accounted for the maximum weight ratio, indicating that ADC was more homogeneous than SCC.…”
Section: Discussionsupporting
confidence: 90%
“…Caiyue et al (28) found that the machine learning-integrated 18 F-FDG PET/CT radiomics model based on the clinical characteristics of 315 patients with NSCLC could efficiently predict the pathological set of SCC and ADC, with an AUC of 0.932 (95% CI: 0.900-0.964) and 0.901 (95% CI: 0.840-0.957) in the training set and testing set, respectively. In our previous study (15), 61 patients with ADC or SCC were divided into a training group and a testing group at the ratio of 7:3, and the features selected from preoperative PET/MRI images were applied to create a prediction model. It was found that the AUC value for classifying ADC and SCC was 0.886 (95% CI: 0.787-0.985) and 0.847 (95% CI: 0.648-1.000) in the training and testing groups, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations